The Role of Efflux Pumps in the Transition from Low-Level to Clinical Antibiotic Resistance - Anna Elisabeth Ebbensgaard; Anders Løbner-Olesen; Jakob Frimodt-Møller (MDPI AG, 2020)
Antibiotic resistance is on the rise and has become one of the biggest public health challenges of our time. Bacteria are able to adapt to the selective pressure exerted by antibiotics in numerous ways, including the (over)expression of efflux pumps, which represents an ancient bacterial defense mechanism. Several studies show that overexpression of efflux pumps rarely provides clinical resistance but contributes to a low-level resistance, which allows the bacteria to persist at the infection site. Furthermore, recent studies show that efflux pumps, apart from pumping out toxic substances, are also linked to persister formation and increased spontaneous mutation rates, both of which could aid persistence at the infection site. Surviving at the infection site provides the low-level-resistant population an opportunity to evolve by acquiring secondary mutations in antibiotic target genes, resulting in clinical resistance to the treating antibiotic. Thus, this emphasizes the importance and challenge for clinicians to be able to monitor overexpression of efflux pumps before low-level resistance develops to clinical resistance. One possible treatment option could be an efflux pump-targeted approach using efflux pump inhibitors.